Molecular characterization of Joubert syndrome in Saudi Arabia - Alazami, Anas M.; Alshammari, Muneera J.; Salih, Mustafa A.; Alzahrani, Fatema; Hijazi, Hadia; Seidahmed, Mohammed Z.; Abu Safieh, Leen; Aldosary, Mazhor; Khan, Arif O.; Alkuraya, Fowzan S. (Human mutation, 2012)
Joubert syndrome (JS) is a ciliopathy that is defined primarily by typical cerebellar structural and ocular motility defects. The genetic heterogeneity of this condition is significant with 16 genes identified to date. We have used a combination of autozygome‐guided candidate gene mutation analysis and exome sequencing to identify the causative mutation in a series of 12 families. The autozygome approach identified mutations in RPGRIP1L, AHI1, TMEM237, and CEP290, while exome sequencing revealed families with truncating mutations in TCTN1 and C5ORF42. Our study, the largest comprehensive molecular series on JS, provides independent confirmation of the recently reported TCTN1, TMEM237, and C5ORF42 as bona fide JS disease genes, and expands the allelic heterogeneity of this disease. Hum Mutat 33:1423–1428, 2012. © 2012 Wiley Periodicals, Inc.